2007
DOI: 10.1002/pssc.200673839
|View full text |Cite
|
Sign up to set email alerts
|

Damage creation in LiF and NaCl crystals irradiated with swift heavy ions at 8 and 300 K

Abstract: Single crystals of LiF and NaCl were irradiated at 8 and 300 K with different ions ( 12 C to 238 U) of MeVGeV energy in the electronic stopping regime. The ion-induced damage was studied by optical absorption, thermo-stimulated luminescence, and scanning force microscopy. The concentration of the color centers depends on the energy loss of the ions. In both crystals, the irradiation with heavy ions (Au, Pb, U) results in a higher F center concentration at 8 K than at 300 K; for light ions (C, Ti, Ni) the oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 13 publications
3
35
0
1
Order By: Relevance
“…This figure demonstrates that the largest part of the excess energy transferred into the lattice is localized within the distances r < 3 nm from the ion trajectory. The maximum lattice heating in this area does not exceed 100 K which is in a good agreement with the experimental results reported in [9]. This agreement proves an applicability of the presented model to description of material excitation in SHI tracks.…”
Section: Tracing Of Atomic Dynamicssupporting
confidence: 90%
See 1 more Smart Citation
“…This figure demonstrates that the largest part of the excess energy transferred into the lattice is localized within the distances r < 3 nm from the ion trajectory. The maximum lattice heating in this area does not exceed 100 K which is in a good agreement with the experimental results reported in [9]. This agreement proves an applicability of the presented model to description of material excitation in SHI tracks.…”
Section: Tracing Of Atomic Dynamicssupporting
confidence: 90%
“…The obtained little heating (~100 K) agrees well with the experiment-based estimations of track heating in irradiated LiF crystals [9].…”
supporting
confidence: 86%
“…Its density q = 2.32 g/cm 3 corresponds to the atomic density n a = 6.9 Â 10 22 1/cm 3 maximum energy of a delta-electron created by such Ca ion is E max = 24.8 keV. It corresponds to the electron velocity V max e ¼ 9 Â 10 7 m=s < V SiO 2 c which is also less that the speed of light in quartz.…”
Section: Resultsmentioning
confidence: 97%
“…[3,4]. In this case numerical simulations can give principle information about major processes governing relaxation of electronic subsystem in SHI tracks.…”
Section: Introductionmentioning
confidence: 97%
“…In order to explain the observed effects of SHI irradiation as formation of nano-hillocks on the surface, creation of stable point-like defects (color-centers), it was found that the parameters of TTM need a special treatment, which would confine the energy inside a narrow track halo for timescales orders of magnitude longer than those given by the usual TTM [4][5][6][7]. For these reasons, electronic confinement usually is introduced via a temperature-dependent electronic diffusivity [5,6] and by fitting an electron-phonon coupling constant [5].…”
Section: Introductionmentioning
confidence: 99%